If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8f = -2f + -10 Reorder the terms: 8f = -10 + -2f Solving 8f = -10 + -2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '2f' to each side of the equation. 8f + 2f = -10 + -2f + 2f Combine like terms: 8f + 2f = 10f 10f = -10 + -2f + 2f Combine like terms: -2f + 2f = 0 10f = -10 + 0 10f = -10 Divide each side by '10'. f = -1 Simplifying f = -1
| 9x=125 | | 2a+12=6 | | 7x=-64 | | 7x+32=-32 | | x=5000 | | a+6=4 | | x=2100 | | 12+56= | | 6=9x | | 0=9x-6 | | -16=8x | | 23=18+5x | | e=9-2e | | 4x=6x-11 | | 40=41+x | | 18y-6=-18 | | 18y-6=-10 | | 6p-5=7 | | 30=15x | | t=15x | | 6y^3-7y^2-7y+6=0 | | 20z-1+36=5z+5 | | 30-x=10+0.5x | | 11=21a | | 6m=x | | 4(-2z-5)-7=10 | | 35-6= | | 100*20= | | 3r+10=2(-3r+8) | | (5x-4)3-5(4-3x)=7x+7(3x-4) | | h-13=78 | | 5p-3tq=2 |